Off the rails [videorecording (DVD)] - Waller, Jordan; Seagrove, Jenny; Preston, Kelly; Dench, Judi, 1934-; Nero, Franco; Miller, Ben, 1966-; Phillips, Sally, 1970-; Dormer-Phillips, Elizabeth (Screen Media, 2022)
Three best friends from college recreate their post-graduation trip across Europe to honor the memory of their friend Anna. Joining Kate, Liz, and Cassie, is Anna's 18-year-old daughter Maddie fulfilling her mother's last wish to have them take this trip with her. When lost passports, train strikes, and romantic entanglements get in their way, they put old feuds aside to complete the journey and remind themselves that they are still at their peak.